1989
DOI: 10.1177/000331978904000404
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Pharmacokinetics of Quinapril

Abstract: Quinapril (Q) and quinaprilat (QT) pharmacokinetics are dose proportional following single oral 2.5- to 80-mg Q doses. Q absorption and hydrolysis to QT is rapid with peak Q and QT concentrations occurring one and two hours postdose, respectively. Peak plasma QT concentrations were approximately fourfold higher than those of Q (923 vs 207 ng/mL following 40-mg Q). Dose-proportional QT area under the curve and dose-independent percent of dose excreted in urine as QT demonstrate that the extent of Q conversion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…After a dose of 2.5 mg p.o. in healthy subjects, the Cmax was 41 (12.7) (SD) ng/ml [1]. In our study mean Cm~x ranged from 63.3 (CAPD patients) to 83.5 ng.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations
“…After a dose of 2.5 mg p.o. in healthy subjects, the Cmax was 41 (12.7) (SD) ng/ml [1]. In our study mean Cm~x ranged from 63.3 (CAPD patients) to 83.5 ng.…”
Section: Discussionsupporting
confidence: 41%
“…The peak plasma concentration of quinaprilat occurred later (4 to 4.7 h) than in healthy subjects (2 h), independent of dose [1]. The tmax reported in CAPD patients after 20 mg was 5.4 (2.5) (SD) h [4] and 4.5 (2.5) (SD) h in chronic HD patients [3].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…l 3 The investigators reported that the HDWLDL cholesterol ratio remained virtually unchanged after 1 year of therapy with quinapril. Serum triglycerides did not increase.…”
Section: Plasma Lipid and Lipoprotein Levelsmentioning
confidence: 99%